Local politicians 1993 - Total survey - Bäck, Henry (Stockholm University, 1995)
This survey is part of the research programme ´Demokrati i förändring´. The main purpose was to look into changes in the idea of the role as a local politician and in the working conditions of local politicians taking place since the corresponding survey in 1980, ´Local Politicians, 1979-80´ (SSD 0101). The changes are related to ´the local authority reorganisation´ in shape of ´privatisation´ and ´new democratic structures´. The questionnaire, addressed to local authority and county council politicians, contained background information such as age, place of residence, marital status, education, citizenship, occupation, political party and for how long time one had been a member of the party, and time for first assignment. Other questions dealt with the opinion of the general public regarding local politicians; the attitude of people around the respondent towards the political commitment; and contacts with the general public, mass media, associations, organisations, and companies concerning local issues during the last year. For a number of local authority areas the respondent had to state if it is important to increase the local authority commitment, if it is enough as it is, or if it could be reduced. For a number of statements about how it ought to come about in politics the respondents had to state if they agreed or not. A number of questions concerned conflicts between different activities of the elected representative; time required for different activities; membership of the party organisation council, and other organisation commissions; and how to vote when there is a conflict between the opinion of the councillor, the party, and the general public. The respondents also had to state how important the various moments in the decision-making process are in their own municipality; how much the opinions of the other political parties usually differs from their own party; qualities the parties ought to consider when nominating candidates; and to what extent the space of action is influenced by external circumstances. For a number of statements about the role of local politicians and local government officers in the decision-making process, and about the conditions for men and women in society, the respondents had to state if they agreed or not. The respondents also had to decide on a number of proposals discussed to make the local authority organisation and the decision-making process more efficient; and if they agreed or not in a number of statements about political cooperation between countries, and local consequences of a Swedish approach toward the European Union.

Undersökningen ingår i forskningsprogrammet 'Demokrati i förändring' och avsätter i första hand data för delprogrammet om väljare, partier och politiker. Syftet är i första hand att undersöka förändringar i kommunalpolitikernas rolluppfattning och arbetsförhållanden sedan 1980 års motsvarande undersökning Kommunalpolitikerundersökningen 1979-80 (SND 0101). Förändringarna relateras till 'den kommunala nyordningen' i form av 'privatisering' och 'nya demokratiska strukturer'.
Enkäten, som riktade sig till kommunal- och landstingspolitiker, innehöll bakgrundsuppgifter såsom ålder, bostadsort, civilstånd, utbildning, medborgarskap, yrke, hur länge man varit medlem av sitt politiska parti och när man fick sitt första kommunala uppdrag. Andra frågor tar upp allmänhetens inställning till kommunal-/landstingspolitiker, den närmaste omgivningens inställning till det egna engagemanget som politiker och kontakter med allmänhet, massmedia, föreningar, organisationer och företag i kommunala frågor under det senaste året. För ett antal kommunala områden fick respondenten ange om det var angeläget att kommunen gör mera, om det var bra som det är eller om det kommunala engagemanget kunde minskas. Respondenterna fick även ange om man instämde eller ej med ett antal påståenden om hur det går till eller bör gå till i politiken. En serie frågor berör konflikter mellan de förtroendevaldas olika aktiviteter, hur mycket tid de olika aktiviteterna kräver, styrelseuppdrag i partiorganisationer samt övriga organisationsuppdrag och hur en ledamot skall rösta då det uppstår en konflikt mellan den egna, fullmäktigegruppens och allmänhetens uppfattning. Respondenterna fick ange vilken betydelse för innehållet i den ekonomiska planeringen de olika momenten i beslutsprocessen har i den egna kommunen, hur mycket de övriga politiska partiernas uppfattning i kommunala frågor brukar skilja sig från det egna partiet, vilka egenskaper partierna bör ta hänsyn till vid nominering av kandidater och i vilken utsträckning kommunens handlingsutrymme påverkas av olika yttre omständigheter. För ett antal påståenden om politiker och tjänstemäns roll i beslutsfattandet och om mäns och kvinnors villkor i samhället fick respondenterna ange om de instämde eller ej. Respondenterna fick även ta ställning till ett antal förslag som diskuteras för att göra den kommunala organisationen och beslutsprocessen i den kommunala förvaltningen effektivare samt ange om man instämde eller ej i ett antal påståenden om politiskt samarbete över nationsgränsen och lokala konsekvenser av Sveriges närmande till EG.
Enkätundersökningen är kompletterad med en studie innehållande uppgifter om uppdrag, födelseår, svenskt eller annat medborgarskap samt yrke (SEI) för samtliga förtroendevalda inom de 28 primärkommunerna och fyra landstingen.
Kommunalpolitikerundersökningen 1993 - Totalundersökningen
Keywords: INTERNAL POLITICS; INRIKESPOLITIK; Political behaviour and attitudes; Politiska beteenden och attityder; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap